Induction of Intestinal Graft-versus-host Disease and Its Mini-endoscopic Assessment in Live Mice - Buchele, Vera; Büttner-Herold, Maike; Vogler, Tina; Neurath, Markus; Hildner, Kai (Journal of Visualized Experiments, 2019)
Acute graft-versus-host disease (GvHD) represents the most severe complication that patients previously undergoing allogeneic hematopoietic stem cell transplantation (allo-HCT) face and is frequently associated with a poor clinical outcome. While, for instance, GvHD manifestations of the skin are usually responsive to established immune-suppressive therapies and are, hence, not taking a fatal course, the presence and the intensity of intestinal GvHD, especially of the mid-to-lower parts of the gut, strongly influence the outcome and overall survival of patients with acute GvHD. Therapeutic options are essentially limited to the classic immune-suppressive agents yielding only moderate disease-mitigating effects. Hence, detailed knowledge about the tissue-resident immune cascade, changes in the intestinal microbiota, and the stromal response prior, upon, and after intestinal GvHD onset are urgently needed to understand the events and mechanisms underlying its pathogenesis and to develop innovative therapeutic options. Murine models of GvHD are frequently employed to identify and functionally assess molecules and pathways putatively driving intestinal GvHD. However, means to specifically monitor and evaluate intestinal inflammation over time are essentially lacking since established scores to assess and grade acute GvHD are routinely comprised of various parameters which rather reflect systemic GvHD manifestations. The detailed evaluation of intestinal GvHD has been restricted to studies using euthanized mice, thereby essentially excluding longitudinal (i.e., kinetic) analyses of the colonic compartment under a given experimental condition (e.g., antibody-mediated blockade of a proinflammatory cytokine) in live mice (i.e., in vivo). The mini-endoscopic in situ assessment of the distal colon of alloHCT-treated mice described here allows a) a detailed macroscopic evaluation of different aspects of intestinal inflammation and b) the option to collect tissue samples for downstream analyses at various time points over the course of the observation period. Overall, the mini-endoscopic approach provides a major advance in preclinical noninvasive monitoring and assessment of intestinal GvHD.
CRIS-Team WoS Importer:2019-04-12